Efficacy and safety of onabotulinumtoxinA in the treatment of medication overuse headache: a systematic review - Lang, Hui; Peng, Cheng; Wu, Kongyuan; Chen, Xiwen; Jiang, Xin; He, Li; Chen, Ning (Frontiers in Neurology, 2024)
Purpose Medication overuse headache (MOH) is a chronic headache caused by regular overuse of medications. OnabotulinumtoxinA (BoNTA) is used for preventive treatment of MOH. However, its efficacy and safety remain controversial. Methods Seven online databases (Cochrane Library, Embase, Medline, PubMed, China National Knowledge Infrastructure, Wanfang data, and Chinese BioMedical Literature Database) were searched for relevant articles published between January 2002 and March 2024. We included randomized controlled trials (RCTs) and cohort studies on the treatment of MOH using BoNTA versus a placebo or other active treatments. Results We retrieved 487 articles in the database search. Of these, four eligible RCTs were identified after detailed screening. A total of 1,259 patients with MOH (622 patients treated with BoNTA, 607 with placebo, and 30 with topiramate) were included in the four RCTs. We found that BoNTA significantly reduced headache frequency compared with placebo (mean difference, 1.89; 95% confidence interval (CI), 1.11–2.67; I2 = 0%; p < 0.001). There was no significant difference between BoNTA and the placebo in terms of secondary outcomes, which included reductions in acute medication intake (MD, 1.30; 95% CI, −1.18–3.78; I2 = 0%; p = 0.30), Migraine Disability Assessment questionnaire scores (MIDAS, MD, −4.04; 95% CI, −29.36–21.28; I2 = 0%; p = 0.75), and Headache Impact Test scores (HIT-6, MD, 0.03; 95% CI, −1.77–1.83; I2 = 0%; p = 0.97). BoNTA was more likely to cause adverse events (OR, 1.87; 95% CI, 1.45–2.42; I2 = 0%; p < 0.001) than placebo. Conclusion The results of this study show that BoNTA reduces headache frequency and is effective for the treatment of MOH. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022315845.